Modeling and coordination control of AC/DC hybrid microgrids - Zhang, Zhe (Nanyang Technological University, 2022)
Three-phase alternating current (AC) has dominated the global power systems for over a century due to advantages such as readily transforming voltages with different levels, high-efficiency generation, transmitting power over long distances, etc. However, direct current (DC) power systems have recently gained popularity because they enable the more efficient and dependable integration of renewable energy sources such as solar, wind, fuel cells, and battery energy storage systems (ESSs). Thus, interlinking AC and DC subgrid power systems to be hybrid AC/DC microgrids presents a promising solution to energy and environmental issues.